EFFECTS OF CONTAINMENT ON PERCUTANEOUS HIPOXIA AFTER ENDOTRACHEAL SUCTIONING IN NEONATES - Salazar González, Bertha Cecilia; Whetsell, Martha V.; Ruvalcaba Rodríguez, Diana; Rojas Garza, Irma Guadalupe; Cervantes Valero, Noemí (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: The purpose was to verify the effectiveness of containment using pre-suction oxygen bag versus non pre-suction oxygen bag on recovery time of percutaneous hipoxia values after endotracheal suctioning of premature infants with respiratory distress syndrome. Containment is proposed as an aid to induce relaxation in premature babies; it is a technique that limits a neonate’s movements resembling the uterus environment. Material and methods: A crossover design with one group was used, each neonate serve as its own control. This study was conducted in 30 neonates who had been born between 26 and 36 weeks gestational age, in a Neonatal Intensive Care Unit of a Social Security’s Hospital in Monterrey. Each neonate was observed during four suction procedures: two without containment and two with containment. Results: The neonate’s weight ranged from .790 to 3.275Kg., according to their medical chart 25 neonates experienced moderate respiratory distress syndrome. The ANOVA test (F(3,87), = 7.77, p < 0.001) showed that the means were signiﬁcantly lower for the two containment procedures The recovery time was signiﬁcantly reduced on the two containment procedures. Conclusions: Results indicate that containment may help on recovery time of percutaneous hipoxia values after suctioning of premature infants with respiratory distress syndrome.